The role of esophagectomy in the management of Barrett's esophagus with high‐grade dysplasia. Issue 1 (18th August 2020) - Badgery, Henry; Read, Matthew; Winter, Nicole N.; Taylor, Andrew C. F.; Hii, Michael W.
Abstract: Barrett's esophagus (BE) with high‐grade dysplasia (HGD) has previously been a routine indication for esophagectomy. Recent advances in endoscopic therapy have resulted in a shift away from surgery. Current international guidelines recommend endoscopic therapy for BE with HGD irrespective of recurrence or progression of dysplasia. Current guidelines do not address the ongoing role of esophagectomy as an adjunct in the setting of failed endoscopic therapy. This review examines the role of esophagectomy as an adjunct to endoscopy in the management of patients with BE and HGD, with a specific focus on patients with persistent, progressive, or recurrent disease, disease resistant to endoscopic therapy, in patients with concomitant esophageal pathology, and in those patients in whom lifelong surveillance may not be possible or desired.